EMPLOYEE PERFORMANCE BASED ON WORK DISCIPLINE AND WORKLOAD AT PT JALUR NUGRAHA EKA KURIR (JNE EXPRESS) MAIN BRANCH, BOGOR CITY - Sunarto, Ading; Agrasadya, Agrasadya; Abidin, Ali Zaenal (International Journal of Multidisciplinary Research and Literature, 2025)
This study aimed to determine how much work discipline and workload influence employee performance at PT. Jalur Nugraha Eka Kurir (JNE Express) Main Branch, Bogor City. The method used in this study is quantitative analysis with a population of employees at PT. Jalur Nugraha Eka Kurir (JNE Express) Main Branch, Bogor City, as many as 97 respondents or with a sample with data collection techniques by distributing questionnaires. The data analysis methods used in this study are (validity test, reliability test, and classical assumption test), quantitative descriptive analysis, simple and multiple regression analysis, and determination coefficient analysis, hypothesis test (T and F tests). The results of the study of the work discipline variable have a regression coefficient value of 0.996, a t-count value of 18.643 greater than 1.6610 (18.643> 1.6610), and a significance value of 0.000 less than 0.05 (0.000 <0.05). It means that Ha is accepted and Ho is rejected. The results of the workload variable study have a regression coefficient value of (-3.698), a t-value of (-3.698) more minor than 1.6610 (-3.698 <1.6610) and a significance value of 0.000 smaller than 0.05 (0.000 <0.05). Ha is accepted, and Ho is rejected. Work discipline and workload positively and significantly influence employee performance at PT. Jalur Nugraha Eka Kurir (JNE Express) Main Branch, Bogor City, with an F-value of 323.910 greater than the F-table of 3.09 (323.910> 3.09) and a significance value of 0.000 smaller than 0.05 (0.000 <0.05)